2016
DOI: 10.1080/15592294.2016.1178418
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation of loci within ABCG1 and PHOSPHO1 in blood DNA is associated with future type 2 diabetes risk

Abstract: Identification of subjects with a high risk of developing type 2 diabetes (T2D) is fundamental for prevention of the disease. Consequently, it is essential to search for new biomarkers that can improve the prediction of T2D. The aim of this study was to examine whether 5 DNA methylation loci in blood DNA (ABCG1, PHOSPHO1, SOCS3, SREBF1, and TXNIP), recently reported to be associated with T2D, might predict future T2D in subjects from the Botnia prospective study. We also tested if these CpG sites exhibit alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
192
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 164 publications
(215 citation statements)
references
References 33 publications
18
192
1
Order By: Relevance
“…Indeed, Willmer and colleagues highlighted differential methylation at sites within the PHOSPHO1 gene as a potentially useful biomarker for clinical application in the early detection of type‐2 diabetes. Moreover, increased methylation was positively correlated with high density lipoprotein (HDL) concentration in blood and was decreased in muscle tissue from diabetic patients . This relationship with HDL concentration was also reproduced independently in an EWAS focused on serum lipid profiles conducted in a separate cohort .…”
Section: Other Physiological Rolesmentioning
confidence: 63%
See 1 more Smart Citation
“…Indeed, Willmer and colleagues highlighted differential methylation at sites within the PHOSPHO1 gene as a potentially useful biomarker for clinical application in the early detection of type‐2 diabetes. Moreover, increased methylation was positively correlated with high density lipoprotein (HDL) concentration in blood and was decreased in muscle tissue from diabetic patients . This relationship with HDL concentration was also reproduced independently in an EWAS focused on serum lipid profiles conducted in a separate cohort .…”
Section: Other Physiological Rolesmentioning
confidence: 63%
“…Several other studies have found intriguing associations between PHOSPHO1 expression and disorders of altered energy metabolism such as diabetes and obesity. Epigenome‐wide association studies (EWAS) have found significant associations between methylation at loci within the PHOSPHO1 and the future risk of type‐2 diabetes in human cohorts . Indeed, Willmer and colleagues highlighted differential methylation at sites within the PHOSPHO1 gene as a potentially useful biomarker for clinical application in the early detection of type‐2 diabetes.…”
Section: Other Physiological Rolesmentioning
confidence: 99%
“…A CpG site ( cg06500161 ) within the ABCG1 locus becomes hypermethylated as a consequence of increased BMI in >10,000 people of European and Asian Indian ethnicity and across different tissues including blood, adipocytes, and liver . Most importantly, in further longitudinal analyses (n = 2664), baseline methylation of ABCG1 predicted the onset of Type 2 Diabetes mellitus 7 years later with higher predictive value than standard risk factors such as obesity, fasting glucose, and hemoglobin A1c . Strikingly, 1 other study found that this particular CpG of ABCG1 was differentially methylated in sperm cells from obese vs lean men and reverted to lean‐type levels after weight loss surgery …”
Section: Epigenetics and Personalized Healthmentioning
confidence: 91%
“…52 Most importantly, in further longitudinal analyses (n = 2664), baseline methylation of ABCG1 predicted the onset of Type 2 Diabetes mellitus 7 years later with higher predictive value than standard risk factors such as obesity, fasting glucose, and hemoglobin A1c. 53 Strikingly, 1 other study found that this particular CpG of ABCG1 was differentially methylated in sperm cells from obese vs lean men and reverted to lean-type levels after weight loss surgery. 54 The big question now is whether we are ready for personalized nutrition based on nutrition genomics.…”
Section: Epigenetics and Personalized Healthmentioning
confidence: 93%
“…1,7 To better understand how to hinder disease progression, it has become important to find reliable biomarkers for early intervention. 8 Biomarkers can be any biologic characteristic that can be identified and/or monitored during the progression of a disease. 9 This includes non-invasive measurements such as those currently used for identifying risk for the progression to type 2 diabetes and cardiovascular disease, such as high body mass index (BMI) and blood pressure.…”
Section: Introductionmentioning
confidence: 99%